Transformasi Kurikulum dan Tantangan Pembelajaran Matematika: Analisis Perbandingan Kurikulum 2013 dan Revisi Kurikulum 2013 di Indonesia - Indriani, Ulfa Dwi; Priatna, Nanang; Dahlan, Jarnawi A. (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
The transformation from the 2013 Curriculum (K–13) to the Revised 2013 Curriculum (K–13R) in Indonesia represents a significant shift in mathematics education. This study aims to analyze the differences between K–13 and K–13R through six key aspects: (1) curriculum structure and competency formulation, (2) pedagogical paradigm including the implementation of Higher Order Thinking Skills (HOTS), (3) emphasis on literacy and numeracy, (4) teacher readiness and classroom implementation, (5) availability and contextual quality of textbooks and learning media, and (6) student learning outcomes based on PISA and national assessment data. Adopting a qualitative descriptive-comparative approach, this study uses document analysis to explore official curriculum guidelines, textbooks, and supporting literature. The findings reveal that K–13R introduces more structured and concrete competencies, increases focus on contextual and HOTS-based learning, and places greater emphasis on numeracy skills. Nevertheless, classroom implementation remains problematic due to gaps in teacher preparedness, lack of relevant instructional materials, and insufficient understanding of authentic assessments. These results highlight the need for integrated curriculum planning, sustainable teacher training, and contextual resource development to realize the intended transformation.